(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
Lipoma is a benign tumor composed of adipose tissue and is one of the most common soft tissue tumors in humans. Although typically asymptomatic, lipomas can sometimes cause discomfort depending on their size and location. This article aims to explore various aspects of lipomas, including their etiology, clinical manifestations, diagnostic methods, and management approaches.